Rubella seroprevalence using residual samples from the South African measles surveillance program: a cross-sectional analytic study - Motaze, N. V. (Hum Vaccin Immunother, 2020)
Introduction: South Africa is yet to introduce rubella-containing vaccines (RCV) into its routine immunization schedule. Selecting the target population when introducing RCV should take into account the ages of susceptible individuals in the population. We aimed to determine the seroprevalence of antibodies to rubella and characterize immunity gaps among individuals of all ages in South Africa. Methods: We tested for rubella immunoglobulin G (IgG) antibodies with a commercial enzyme-linked immunosorbent assay. We used residual samples collected from 2016 through 2018 as part of the national measles surveillance program. We only tested samples that were negative for measles and rubella immunoglobulin M (IgM) and explored the association between rubella susceptibility (IgG negative) and predictor variables (year of sample collection, age, sex, and province of residence) using logistic regression analysis. Results: We obtained results for 6057 records. Rubella susceptibility was highest among Individuals aged zero to 11 months (81.9%), followed by children 1 to 5 years old (71.5%), 6 to 10 y old (40.9%) and 11 to 15 y old (31.25) while the smallest proportion of susceptible individuals was among those 16 to 49 y old (19.9%). Females were less likely to be susceptible to rubella compared to males (OR = 0.79 (95%CI: 0.71–0.87), P < .001) in unadjusted analysis but this effect was not observed after adjusting for age and province. In multivariable logistic regression, age (OR = 6.24 (4.52–8.63), P < .001) and province of residence (OR = 0.97 (95%CI: 0.95–0.99), P = .01) were associated with rubella susceptibility. Conclusion: In the absence of rubella vaccination in the Expanded Program on Immunization in South Africa, the bulk of individuals susceptible to rubella are children under 16 y old. About 20% of individuals 16 to 49 y old are susceptible to rubella. This susceptibility gap must be born in mind during RCV introduction.